2021
DOI: 10.3389/fonc.2021.763381
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Combined With Big Data to Predict Lymph Node Involvement in Prostate Cancer: A Population-Based Study

Abstract: BackgroundA more accurate preoperative prediction of lymph node involvement (LNI) in prostate cancer (PCa) would improve clinical treatment and follow-up strategies of this disease. We developed a predictive model based on machine learning (ML) combined with big data to achieve this.MethodsClinicopathological characteristics of 2,884 PCa patients who underwent extended pelvic lymph node dissection (ePLND) were collected from the U.S. National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The DCA plot also indicated that the XGBoost algorithm had the highest net benefit across the entire range of threshold probabilities compared with the other three predictive models. 27 This algorithm has also been reported to be effective in predicting the prognosis of patients with esophageal cancer, 25 non‐small‐cell lung cancers experiencing bone metastasis, 28 and osteosarcoma. 29 While the above studies used data from the SEER database, a multi‐institutional retrospective study was designed to construct and compare different ML models including LR, SVM, DT, RF, XGBoost, and LightGBM to predict survival in stage I–II CC patients who underwent complete resection in a real‐world setting.…”
Section: Discussionmentioning
confidence: 98%
“…The DCA plot also indicated that the XGBoost algorithm had the highest net benefit across the entire range of threshold probabilities compared with the other three predictive models. 27 This algorithm has also been reported to be effective in predicting the prognosis of patients with esophageal cancer, 25 non‐small‐cell lung cancers experiencing bone metastasis, 28 and osteosarcoma. 29 While the above studies used data from the SEER database, a multi‐institutional retrospective study was designed to construct and compare different ML models including LR, SVM, DT, RF, XGBoost, and LightGBM to predict survival in stage I–II CC patients who underwent complete resection in a real‐world setting.…”
Section: Discussionmentioning
confidence: 98%
“…The clinical application of ML algorithms may facilitate a paradigm shift in the medical field, as these algorithms are efficient, objective, and reproducible when it comes to large amounts of nonlinear data ( 24 , 29 32 ). They also have the potential to improve the quality of early diagnosis, identify disease progression, and increase the likelihood of predicting patient-specific outcomes ( 25 , 33 , 34 ). These advantages can facilitate the sharing of information for decision-making between clinicians and patients and promote efficient planning and visualization of the use of healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning (ML), as an important branch of artificial intelligence, can continuously optimize the performance of predictive or diagnostic models by learning and analyzing data, and can handle non-linear relationships better than traditional statistical scores. As a result, ML-based models have great potential for the diagnosis and prognosis of diseases ( 23 25 ). Therefore, our goal was to develop a new decision-support ML model based on real-world data for diagnosing PCa in patients with PSA levels ≤20 ng/mL.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the components of artificial intelligence, ML has been widely used in clinical practice, such as for epidemic prediction (23, 24), and survival analysis (25, 26). ML models have also been proposed for the prediction of lymph node metastasis in a variety of malignancies (27,28). Based on these promising clinical applications of ML models, the present study aimed to develop and validate a novel ML-based model for predicting the risk of early-stage ILNM in patients with SCCP.…”
Section: Introductionmentioning
confidence: 99%